The challenge of measuring innovation types: A systematic literature review - Alina Stundziene; Vaida Pilinkiene; Mantas Vilkas; Andrius Grybauskas; Mantas Lukauskas (Journal of Innovation & Knowledge)
Measuring innovation has long posed a significant challenge and has been the subject of extensive scientific research. Various definitions and measures of innovation exist, and each measurement approach faces limitations. This research aims to conduct a systematic literature review to expose the tendencies in measuring various types of innovation, thereby revealing different approaches, challenges, and limitations. This paper systemises and groups indicators, highlighting similarities and differences in measuring various innovation types. The systematic literature review includes 172 papers from the WoS Core Collection and Scopus databases, presenting innovation indicators across nine types of innovation: product, process, service, technological, management (or organizational, administrative), business model, supply chain, green (or environmental, eco), and open innovation. The analysis reveals that researchers often employ a broad range of indicators, many of which are not even closely aligned with specific innovation types. Accordingly, this paper offers recommendations for selecting indicators tailored to innovation type.